Development of Learning Tools Based on the Think Pair Share Learning Model to Improve Metacognition Abilities of Junior High School 4 Panyabungan - Rahmadani, Ulfy; Nasution, Hamidah; Mariani, Mariani (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
This study aims to describe the validity, usability, and efficacy of learning tools based on the Think-Pair-Share learning model, the improvement of students' mathematical metacognition and mathematical communication skills through the use of the developed learning tools, and the process of students' answers to questions pertaining to mathematical metacognition and communication skills. This study is development research employing a four-dimensional development model. Validation and observation sheets, Student Books, Mathematical Metacognition Tests, and Mathematical Communication Tests are the research instruments. Trial I was conducted on students in class VIIIA, and Trial II was conducted on students in class VIIIB at SMP Negeri 4 Panyabungan. From the findings of this study, it was determined that: (1) The developed Think Pair Share learning tools including BS, LKPD, TKMM, and TKKM were included in the valid category; (2) The practicality of the Think Pair Share-based learning device that was developed revealed that: the device could be used with a few revisions and the results of observations of the implementation of the learning device in class revealed that the average practical value, the r-value, was greater than 0.5; and (3) The validity of the Think In trial II, the pre-test was 20.83 percent and the post-test was 87.50 percent; more than 80 percent of students gave positive responses to the learning tools developed; and more than 85 percent of each component of student involvement demonstrated that students were actively engaged in learning; (4) Students' mathematical metacognition and communication abilities increased using the developed Think Pair Share-based learning tool, with an N-gain score of 0.54 for mathematical metacognition and an N-gain score of 0.54 for communication ability.